Presentación: Los Efectos de la reconducción Presupuestal experiencia de caso Sonora 2012 - González Beltrones, Adria Velia (UNIVERSIDAD DE SONORA, 2019)
In the normative framework of international order budget prolongation is a transitional measure, in order to be valid the principle of legality in the income for contributions and the use of public resources through the establishment of an exception to the principle of annuality of systems that establish income and expenses authorized for the public sector The experience of budget prolongation in Sonora in fiscal 2012, not should be repeated, therefore, it must be legislated in order to delete the figure of budget prolongation and political actors to assume their responsibility in the exercise of its functions Similarly, the procedures of responsibilities should be initiated: administrative, political, criminal and patrimonial responsibility, if so, against public servants involved.